Pengaruh latihan kotak plyometrik terhadap kekuatan kaki pada pemain sepak bola muda - Umam, Baha'u Adzanil; Agung Pratama, Budiman; Muharram, Nur Ahmad (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this study was to see the effect of plyometric box drill innovation on youth players at a leg power in soccer. This study used a quantitative approach, the type of research was experimental research, the research design used a non-rondomized group pretest-posttest, the sample numbered 65 players, while the leg power data was collected using a digital jump meter test instrument. The data gathered from participants were analyzed using SPSS software version 24, applying paired sample t-tests and independent sample t-tests with a significance level of 0.05. The results indicated that the two-tailed significance value was 0.000, which is below 0.05. This outcome suggests that the plyometric box drill innovation for youth soccer players had a statistically significant effect. The conclusion of this study states that the innovative plyometric box drill developed for youth soccer players at soccer schools in Tuban can increase leg power. This study showed that the plyometric box drill significantly improved the leg strength of young soccer players, which can be applied as an innovative training method in local soccer schools. The findings provide a basis for developing plyometric-based training programs that are more effective in preparing young players for the physical challenges in football.